Relationship of mountain sickness to physical fitness and exercise intensity during ascent - Bircher, Hans Peter; Eichenberger, Urs; Maggiorini, Marco; Oelz, Oswald; Bärtsch, Peter (Wilderness & environmental medicine, 1994)
The purpose of the study was to investigate whether susceptibility to acute mountain sickness (AMS) and high-altitude pulmonary edema (HAPE) is related to differences of physical fitness and /or the level of exercise during ascent. Work capacity at a heart rate of 170 min−1 (PWC170) was assessed on a bicycle ergometer prior to high-altitude exposure, and the heart rate was continuously registered during the ascent from 3610 to 4559 m in 41 mountaineers. During the subsequent stay of 3 days at 4559 m, 12 subjects developed AMS, 13 subjects showed radiographic evidence of HAPE, and 16 subjects remained without significant illness. PWC170 (group means between 238 and 247 W) and heart rate during ascent (group means between 134 and 141 min−1) did not significantly differ between these groups. PWC170 correlated negatively with two independent symptoms scores (clinical score, environmental symptom questionnaire) on day 3 at 4559 m, whereas heart rate during ascent correlated positively only with clinical score on days 2 and 3 at 4559 m. Correlations, however, were minor, with correlation coefficients of r=0.32-0.43 (p<0.05-0.01). These results indicate that physical fitness or exercise intensity during ascent were of minor importance for the development of AMS and HAPE in our subjects.